Global, Regional, and National Burden and Trends of Soft Tissue and Other Extraosseous Sarcomas From 1990 to 2021 - Rui Zhu MD; Ziyuan Shen PhD; Haijuan Zhu MD; Jisen Zhang MD; Xing Xing MS; Shengyou Wang MD; Jialiu Fang MD (Cancer Control, 2025)
Introduction: Soft Tissue and Other Extraosseous Sarcomas (STOES) represent a rare and heterogeneous group of malignancies with significant clinical challenges due to their complexity and aggressiveness. Despite their low prevalence, the global impact of STOES is substantial, necessitating a detailed examination of their epidemiology and disease burden. Methods: This comprehensive analysis utilized data from the Global Health Data Exchange (GHDx) covering the years 1990 to 2021. We assessed the incidence, prevalence, mortality, and Disability-Adjusted Life Years (DALYs) for STOES, categorized by location, sex, and socio-demographic indices. Statistical methods included Estimated Annual Percentage Change (EAPC), Spearman correlation analysis, and Bayesian age-period-cohort modeling. Findings: In 2021, STOES cases reached a global prevalence of 480,473, a significant increase from 1990. High Socio-Demographic Index (SDI) regions exhibited the highest age-standardized incidence and prevalence rates (ASIR and ASPR) at 2.05 and 10.61 per 100,000 population, respectively. Notably, significant increases were also observed in Central Asia, Central Europe, and Southern Sub-Saharan Africa. Males consistently showed higher disease rates than females. The decomposition analysis highlighted population growth and aging as primary drivers of the observed trends. Forecasting suggests a decline in the global STOES burden by 2030, though disparities will persist, particularly among males. Conclusion: The study reveals critical geographic and demographic disparities in the burden of STOES, underscoring the ongoing higher risk among males and in certain global regions. Despite projected declines in overall disease burden by 2030, substantial disparities are expected to persist, necessitating targeted public health interventions and robust policies to effectively mitigate these differences and enhance global health outcomes.